TELLURIC, GEOMAGNETIC, AND AURORAL ACTIVITY ON ARCTIC DRIFTING STATIONS AND AT PT. BARROW. - Hessler,Victor P. (1970)
The report presents results of scaling and analysis of telluric, magnetic and auroral data taken at Point Barrow, and on Arctic drifting stations Charlie, Arlis 1 and Arlis 3. Scalings of hourly range in telluric current activity for Point Barrow are presented for the epoch August 1961 through December 1965. Similar scalings are presented for the 2 to 4 month data recording periods for each of the three drifting stations. Studies of the diurnal variation of telluric current activity with respect to the auroral oval show relatively good correlation. However, the differences suggest the need for more study in relating the telluric activity to the auroral activity and, perhaps, in the delineation of Akasofu's approximate auroral ovals. The relative amplitude of telluric activity at College, Barrow and Charlie is in the order of 13 to 5 to 1. (Author)